Innovation in Metal Casting Processes: A Review of Metal Matrix Nanocomposites in Metal and Bimetal Castings - Tayyab Subhani; Mohamed Ramadan; Naglaa Fathy; Abdel Khaliq; K. S. Abdel Halim (Crystals)
The arrival of nanotechnology in the field of metal castings is considered a promising approach to significantly improve the quality, performance and lifetime of castings. A better understanding of the implementation of nanotechnology in the metal casting process and its dynamics is essential for the successful production of metal matrix nanocomposite castings. This review focuses on past and present techniques for metal matrix nanocomposite castings to facilitate future fabrication processes and improve the performance of casting products. The advantages, limitations, difficulties and optimal processing conditions of nanocomposite castings are presented and thoroughly discussed. Both types of metal matrix nanocomposites (i.e., ferrous and nonferrous metallic matrices, are discussed in the present review), as well as nanocomposites in the working surface layer and interlayer of bimetallic materials. Significant improvements in the surface microstructure and shear strength of bimetallic bearings are achieved using nanoparticles as additions to the surface working layer and interlayer areas. Special emphasis is given to the factors affecting these fabrication processes in achieving high-quality products. The dispersion of nanoparticles in the metallic matrix is another critical issue, which is discussed comprehensively. Moreover, the strengthening mechanisms that evolve due to the incorporation of nanoparticles in the metallic matrices, which deserve separate attention, are discussed. The economic and political factors that simultaneously lead to evolutionary and drastic changes in metal matrix nanocomposite castings are also considered. Finally, the present article indicates future fabrication routes and describes the development of metal matrix nanocomposite castings under the influence of nanotechnology after incorporating the novel casting opportunities presented by nanotechnology.